Children’s Functioning in Difficult Situations in the Contemporary World - Cywińska, Małgorzata; Mickiewic, Adam (European Journal of Social Science Education and Research, 2021)
Stress is an integral part of our lives. It also applies to our childhood. That is why it is so important to know how children cope with stress (how they learn coping strategies) and to equip them with the competences to cope constructively with stressful situations throughout life. This article describes strategies for coping with stress that are characteristic for children at the end of early school education. They have been identified in the course of my own research aimed at characterizing child stress and relate to a fragment of research activities aimed at 8- and 9-year-old children. The research established that in some children the developmental process of coping with stress has started: children look for, investigate, and think how to cope with difficulties. In this struggle, however, they focus on people who could be a source of support for them in coping with stressful situations. Among children’s stress coping strategies, an important role is also played by emotionally focused strategies, which are aimed at reducing negative emotions and arousing positive emotions. Contemporary times show how important it is to develop, from the earliest period of an individual’s life, competences in dealing with difficult situations, with stressful situations. Development of emotional intelligence, including emotional self-awareness, self-regulation, empathy, creative problem solving, the ability to establish and maintain relationships, including friendship relationships, the development of specific cognitive skills (divergent thinking, cognitive decentration), as well as psychological resilience are the basis of constructive coping with these situations. The family environment, a stable, harmoniously functioning home, as well as educational influence of preschool and early school environment play an enormous role in shaping these competences in children.